Penguatan Tata Kelola Keuangan BUMKam Elseng Koya Koso melalui Pengembangan Aplikasi Pencatatan Transaksi - Annisa Fitriah Mudassir; Yulianti Karoma; Dytha Meninta Nababan; Ade Rezky Nammu; Diana Dwi Febrianti; Nailah Indah Zharifah; Yuan S. Y. Sobolim; Monique I. Rismaully Siregar (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2026)
The Village-Owned Enterprise (BUMKam) of Elseng Koya Koso, which manages a laying hen farming business, plays an important role in supporting the economic independence of the local community. However, its financial management has been conducted manually, resulting in several challenges, including unstandardized transaction recording, difficulties in preparing financial reports, low data accuracy, and limited managerial capacity in utilizing digital technology. This Community Service Program aimed to strengthen the financial governance of BUMKam through the development of a web-based transaction recording application while enhancing the managerial capacity of its administrators in operating the system. The program employed a participatory approach consisting of needs assessment through observation and interviews, application development and implementation, as well as training and technical assistance. The developed application facilitates the recording of income and expenditure transactions, systematic data storage, and the automatic generation of basic financial reports. The results demonstrate that the application was successfully implemented in accordance with the partner's operational needs and significantly improved the efficiency and accuracy of transaction recording, simplified the preparation of financial reports, and minimized recording errors commonly found in the previous manual system. Furthermore, the training program enhanced the administrators' knowledge and practical skills in utilizing digital technology to support business management. Overall, this community service initiative contributed to improving transparency, accountability, and efficiency in the financial governance of BUMKam while promoting digital transformation in community-based enterprises. The proposed model has the potential to be replicated in other Village-Owned Enterprises (BUMDes/BUMKam) with similar business characteristics to strengthen financial governance and support sustainable community-based economic development.